Непропорційне масштабування зображень методом Seam Carving і вибір енергетичних функцій для нього - Шийка, Юрій; Шувар, Роман (Видавництво Національного університету «Львівська політехніка», 2009)
Effective resizing of images, especially when changing the aspect ratio, must be content aware. The Seam Carving method of content aware image resizing (retargeting) consists in deleting of connected pixel paths called seams from the image. Seams vertical or horizontal are built on principle of minimal sum of energy of pixels. Repeatedly deleting or adding such seams in ascending order by energy allows resizing the image with change of the aspect ratio. Energy ofpixels is calculated by applying of energy function (gradient, laplacian et cetera) to the image. Choice of energy function sets the criterion of importance (energies) of pixels, which obviously influences the result of image resizing. Choosing the energy function depending on the type of content of the image enables getting better results of image resizing with change of the aspect ratio.
Keywords: image retargeting; content aware image resizing; Seam Carving; change of the aspect ratio; energy functions; графічні дані; метод Seam Carving; енергетичні функції